Electricity meter area identification technology based on channel coding theory - Yinghai XIE; Yu ZHANG (物联网学报)
Station area identification has always been a problem in the ubiquitous power Internet of things, a new analytical model similar to fading channel was established for the station area identification, and based on the remote on-load voltage regulation function of on-load capacity and voltage regulation distribution transformer, the channel coding theory was applied to solve the problem.In order to identify station area of the smart meters, different special voltage regulation schemes with the properties of repeated coding and block coding were applied synchronously.At the same time, the power consumption information acquisition system was used to collect the voltage of each smart meter in this period.Finally, the recognition of each meter was realized based on the principle of minimum distance of decoding algorithm.The theoretical analysis and test results show that, compared with the traditional technology, the new technology can realize the high accuracy identification of a large number of meters in the on-load capacity and voltage regulation distribution transformer area in the existing power grid system without upgrading, which has high engineering application value.